Perubahan Sosial Masyarakat Desa Raya Kab Simalungun - Adinda Kartika Sari (Jurnal Pendidikan Sosial Indonesia, 2023)
Changes in society can be about social values, social norms, patterns of organizational behavior, the composition of social institutions, layers in society, power and authority, social interactions and so on. Nearly 80% or more of Indonesia's population live in rural areas. Thus, rural areas are not only a source of economic strength. Based on the paper above, a paper was created entitled "Social Change in the Community of Raya Village, Simalungun Regency. The research method that the author used in this study can be reviewed from sources, namely library research (Library Research). The development of social change in the community in Raya Village, Simalungun Regency in the economic field is growing rapidly. This Raya village is passed by the Sumatran causeway which encourages many people to open stalls on the side of the road. However, over time, Raya became the capital of Simalungun Regency, which had a very good impact on the community. The community does not only open stalls but has started to open cafes or restaurants.